INFORMATION TECHNOLOGY AND ITS IMPACT ON THE FINANCIAL PERFORMANCE: AN APPLIED STUDY IN INDUSTRIAL COMPANIES (MINING AND EXTRACTION) - Aldalayeen, Basman Omar; Alkhatatneh, Wahid Rath'n Moh'd; AL-Sukkar, Ahmad Saleh (European Scientific Journal, ESJ, 2013)
This study aimed to identify the impact of using the Information Technology (IT), the financial performance of the industrial companies (Mining and Extraction). The questionnaire was used to collect the data of to achieve the objectives of study and distribute that were following: Assessment Managers, Assistants, Heads of Departments, Administrative Assistant and Workers in Middle Management, the random sample were (176) respondent. The researchers extracted the financial performance indicators data which used from 2009 to 2012, according to the annual report of Amman Stock Exchange for the year 2012 and the Statistical Package of Social Sciences (SPSS) that have been used it to analyze the data and the study found a number of results were most notably. The presence impact of IT with its variables together which were represented as follows (systems complementary, networking capabilities and databases) in the financial performance, light of findings of study recommended a number for recommendations and notably such as providing an effective working environment in industrial companies focusing on the information technology which companies are able to achieve competitive advantages.